Accounting Students' Reflections on a Regional Internship Program - Bonnie Cord; Graham Bowrey; Mike Clements (Australasian Accounting, Business and Finance Journal, 2010)
The opportunity to gain professional industry experience for accounting students while undertaking their undergraduate degree provides them with both a competitive edge in the marketplace and an opportunity to experience the activities undertaken in their chosen profession. Structured experiential learning programs provide students with the practical opportunity to apply their knowledge in an industry context and also to reflect on their personal learning journey. This paper explores the learning contribution of students’ reflection-based assessments in an innovative and flexible internship program based on an e-learning framework. Through a preliminary investigation, it has been identified that after undertaking this internship program, accounting students from an Australian regional university have advanced their learning pertaining to workplace preparedness, understanding and application of accounting principles, generic skill enhancement, and consolidation of accounting as their chosen professional career. The paper suggests that an internship program such as the one examined contributes to the professional accountancy bodies’ and community’s expectations of accounting graduates possessing key cognitive and behavioural skills.
Keywords: Accounting students; Internship programs; Industry experience; Work related learning